Immunopathology of RSV: An Updated Review - Harrison C. Bergeron; Ralph A. Tripp (Viruses, 2021)
RSV is a leading cause of respiratory tract disease in infants and the elderly. RSV has limited therapeutic interventions and no FDA-approved vaccine. Gaps in our understanding of virus–host interactions and immunity contribute to the lack of biological countermeasures. This review updates the current understanding of RSV immunity and immunopathology with a focus on interferon responses, animal modeling, and correlates of protection.